1987
DOI: 10.1104/pp.84.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Root Nodule Carbon Dioxide Fixation

Abstract: Antiserum was prepared in rabbits against purified alfalfa (Medicago sati'a L.) nodule phosphoenolpyruvate carboxylase (PEPC). Immunotitration assays revealed that the antiserum recognized the enzyme from alfalfa nodules, uninoculated alfalfa roots, and from soybean nodules. Tandem-crossed immunoelectrophoresis showed that the PEPC protein from alfalfa roots and nodules was immunologically indistinguishable.The 101 kilodalton polypeptide subunit of alfalfa nodule PEPC was identified on Western blots. The PEPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…4, lanes 1 and 3) showed much less intense bands. These bands correspond to the 104-kD PEPC subunits in alfalfa and lupine root nodules (Miller et al, 1987). The PEPC activity of extracts used for immunoblot analysis was similar to that in Table II, with PEPC activity of proteoid roots being significantly greater than normal roots.…”
Section: Pepc Immunoblot Analysismentioning
confidence: 55%
See 2 more Smart Citations
“…4, lanes 1 and 3) showed much less intense bands. These bands correspond to the 104-kD PEPC subunits in alfalfa and lupine root nodules (Miller et al, 1987). The PEPC activity of extracts used for immunoblot analysis was similar to that in Table II, with PEPC activity of proteoid roots being significantly greater than normal roots.…”
Section: Pepc Immunoblot Analysismentioning
confidence: 55%
“…Protein extracted from alfalfa nodules was used as a positive control for antibody detection. Miller et al (1987) demonstrated that this antibody cross-reacts with the 100-kD lupin nodule PEPC protein and the 100-kD alfalfa root PEPC protein.…”
Section: Sds-page and Western Blot Lmmunoanalysis For Pepcmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfalfa nodules are also reported to have Fd-GOGAT activity (A Suzuki, personal communication). Cross-reaction ofalfalfa nodule NADH-GOGAT antibodies with a polypeptide of comparable mol wt from other legume nodules is consistent with the cross-reaction ofPhaseolus nodule GS (5) and alfalfa nodule phosphoenol-pyruvate carboxylase (PEPC) antibodies (14) with other legume GS and PEPC polypeptides.…”
Section: Glutamate Synthase From Alfalfa Root Nodulesmentioning
confidence: 65%
“…In view of the lack of information on nodule GOGAT, the unavailability of antibodies to the NADH form of the enzyme, and the crucial role of GOGAT in nodule and plant N metabolism, the objectives of this research were to: (a) purify plant NADH-dependent GOGAT from alfalfa root nodules, (b) produce polyclonal antibodies to the enzyme, and (c) characterize the mol wt and some basic kinetic parameters of the enzyme. 400 Amol m-2 s-' as previously described (9,14,27). Before flowering, plants were gently uprooted and washed free of sand.…”
mentioning
confidence: 99%